Gold nanorod-based engineered nanogels for cascade-amplifying photothermo-enzymatic synergistic therapy - Ling Ding; Xiaoshan Wang; Qing Wu; Xia Wang; Qigang Wang (Journal of Pharmaceutical Analysis)
Reactive oxygen species (ROS)-mediated anticancer modalities, which disturb the redox balance of cancer cells through multi-pathway simulations, hold great promise for effective cancer management. Among these, cooperative physical and biochemical activation strategies have attracted increasing attention because of their spatiotemporal controllability, low toxicity, and high therapeutic efficacy. Herein, we demonstrate a nanogel complex as a multilevel ROS-producing system by integrating chloroperoxidase (CPO) into gold nanorod (AuNR)-based nanogels (ANGs) for cascade-amplifying photothermal-enzymatic synergistic tumor therapy. Benefiting from photothermal-induced hyperthermia upon near-infrared (NIR) laser exposure, the exogenous ROS (including H2O2) were boosted by the AuNR nanogel owing to the intercellular stress response. This ultimately promoted the efficient enzyme-catalyzed reaction of loaded CPO combined with the rich endogenous H2O2 in tumor cells to significantly elevate intracellular ROS levels above the threshold for improved therapeutic outcomes. Both in vitro and in vivo studies have verified the cascade-amplifying ROS-mediated antitumor effects, providing feasible multimodal synergistic tactics for tumor treatment.